Determinants of Student Trip Frequency for Campus Transportation Planning: A Case Study of Universitas Muslim Indonesia - Kasim, Muhammad Ridha; Akram, Andi Muhammad; Jihad, Ahmad (Rekayasa Sipil, 2026)
This study explores the factors influencing the frequency of student trips to campus at Universitas Muslim Indonesia (UMI), with particular attention to vehicle group size, residential distance to campus, and selected academic characteristics. The analysis is based on primary survey data collected from 268 respondents and employs multiple linear regression as an exploratory analytical framework to examine relative behavioral influences on campus travel frequency. The results indicate that larger vehicle group sizes are associated with lower individual trip frequencies, while greater residential distance to campus is associated with higher individual trip frequencies. Although the regression model exhibits limited explanatory and predictive power, the findings provide useful insights into dominant student travel patterns and key behavioral drivers. Based on observed average trip frequencies, an indicative estimation of aggregate student trips suggests that campus travel demand is substantially concentrated on weekdays. The study emphasizes that the results should be interpreted as exploratory and planning-oriented rather than predictive forecasts. Nevertheless, the findings offer practical implications for campus transportation planning, particularly in promoting carpooling strategies, optimizing public transport integration, and managing weekday travel demand. These insights are expected to support evidence-based transportation policy development at UMI and comparable university campuses.